2002
DOI: 10.1067/mcp.2002.121370
|View full text |Cite
|
Sign up to set email alerts
|

Shed human enterocytes as a tool for the study of expression and function of intestinal drug‐metabolizing enzymes and transporters

Abstract: The majority of shed human enterocytes collected with a multilumen perfusion catheter were still functionally active and not apoptotic. Harvesting of spontaneously shed enterocytes provides a new tool for studies on expression and function of intestinal proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 24 publications
4
49
0
Order By: Relevance
“…A similar experimental setup to the Loc-I-Gut has been used to collect and study shed human enterocytes (Glaeser et al, 2002). The investigators found that the majority of shed human enterocytes collected were still functionally active, expressed drug-metabolizing enzymes and transporters, and did not show signs of apoptosis.…”
Section: ␤-Glucosidase Activities In the Isolated Small Intestinal Sementioning
confidence: 99%
See 1 more Smart Citation
“…A similar experimental setup to the Loc-I-Gut has been used to collect and study shed human enterocytes (Glaeser et al, 2002). The investigators found that the majority of shed human enterocytes collected were still functionally active, expressed drug-metabolizing enzymes and transporters, and did not show signs of apoptosis.…”
Section: ␤-Glucosidase Activities In the Isolated Small Intestinal Sementioning
confidence: 99%
“…A good correlation exists between the measured jejunal P eff 2 and the fraction dose absorbed of drugs in humans determined by pharmacokinetic studies. Using this technique, the majority of shed human enterocytes collected from an intestinal perfusion were still functionally active and did not show signs of apoptosis (Ahrenstedt et al, 1991;Glaeser et al, 2002). Therefore we not only investigated the transport and metabolism of phytochemicals in the human jejunum but also their effect on the short term changes in mRNA expression of phase II enzymes in shed enterocytes after perfusion.…”
mentioning
confidence: 99%
“…The recommendation is that the parallel-tube model is applied (less stirring of blood than in the liver is anticipated), that f u,bl -data are used, and that in-vitro CL int,GW -data are obtained with human enterocytes or small intestinal mucosa. A considerable portion of the large amount of enterocytes that are shed from the mucosa into the lumen has retained functionality (Glaeser et al 2002), and such cells could be useful for estimation of the in-vitro CL int,GW . It has also been possible to demonstrate that the human intestine in-vitro (Ussing chamber technique) is able to metabolize testosterone (a CYP3A4-substrate) and to have functional P-gp efflux (Sjöberg et al 2000).…”
Section: Prediction Of Systemic Gut-wall Metabolic Clearancementioning
confidence: 99%
“…Other factors that make prediction of CL GW and E GW difficult include inter-and intra-individual variability in enterocyte metabolism, potential contribution by enterocytes that have been sloughed off from the mucosa, efflux, and different expression of drug transporters in mucosal (for example, P-gp, BCRP and MRP2 are efflux proteins in this membrane) and serosal enterocyte membranes (Lin et al 1999;Wacher et al 2001;Doherty & Charman 2002;Glaeser et al 2002). The expression of P-gp along the human intestine has been shown to increase (opposite of CYP3A4 and CYP2C) (Thörn et al 2005;Galetin & Houston 2006).…”
Section: Other Factors That Make Predictions Difficultmentioning
confidence: 99%
“…Improvement in prediction of systemic availability will result upon coupling of the drug-release phase of the ACAT model (Agoram et al, 2001). Sloughed off enterocytes that contribute to intestinal drug metabolism in lumen may need to be modeled (Glaeser et al, 2002). Nonlinearity issues, in terms of intestinal drug-absorptive transporters, metabolic enzymes, and drug efflux transporters, must be considered in drug absorption, especially when the drug is absorbed rapidly to evoke saturation (Tamai et al, 1997;Tam et al, 2003a).…”
Section: Concluding Remarks and Future Modelingmentioning
confidence: 99%